THE ROLE OF THE SENIOR SUPERVISORS TOWARDS THE IMPROVEMENT OF SUPERVISION FROM THE POINT OF VIEW OF THE REGIONAL SUPERVISORS IN OMAN - Sulaiyam ALBalushi, Moatasim Rashid; Sahrir, Muhammad Sabri; Ibrahim, Mohd Burhan (OCERINT International Organization Center of Academic Research, 2019)
This quantitative study discussed the recent developments in the field of educational supervision. The terms of reference and roles of supervisors were identified in their supervisory follow-up and participation in raising academic achievement, providing technical support to help teachers develop their performance. Where the first supervisors are at the top of the technical pyramid; the Department of Educational Supervision had to put them in the care and educational care to improve their technical and specialized performance. The objectives of the study; to discuss the extent to which the first supervisors exercise their supervisory role in the educational directorates in the governorates, and to diagnose the areas that receive more exercise and attention by the supervisors to promote them, and areas that have little practice by the first supervisors to be addressed. The researcher used the descriptive analytical method, on a random sample of (333) first supervisors and supervisors representing the study population at all educational directorates in the governorates of the Sultanate. The findings of the study revealed that: the areas of communication and human relations, planning and organization are the greatest concern of the first supervisors in improving the performance of their supervisors.